2020
DOI: 10.3390/molecules25204636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of µ Opioid Receptor Ligands with Various Functional Properties: PZM21, SR-17018, Morphine, and Fentanyl—Simulated Interaction Patterns Confronted with Experimental Data

Abstract: Molecular modeling approaches are an indispensable part of the drug design process. They not only support the process of searching for new ligands of a given receptor, but they also play an important role in explaining particular activity pathways of a compound. In this study, a comprehensive molecular modeling protocol was developed to explain the observed activity profiles of selected µ opioid receptor agents: two G protein-biased µ opioid receptor agonists (PZM21 and SR-17018), unbiased morphine, and the β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
(45 reference statements)
2
29
1
Order By: Relevance
“…In addition, the conformations of the bound fentanyl are also different in these studies. The dihedral angle between amide carbonyl and aniline was in the trans configuration in the Ricarte, de Waal, and Lipinski poses (de Waal et al, 2020;Lipinski et al, 2019;Ricarte et al, 2021), and cis in the Vo and Podleska poses (Podlewska et al, 2020;Vo et al, 2021) (see the trans and cis definitions in Fig. 1D).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the conformations of the bound fentanyl are also different in these studies. The dihedral angle between amide carbonyl and aniline was in the trans configuration in the Ricarte, de Waal, and Lipinski poses (de Waal et al, 2020;Lipinski et al, 2019;Ricarte et al, 2021), and cis in the Vo and Podleska poses (Podlewska et al, 2020;Vo et al, 2021) (see the trans and cis definitions in Fig. 1D).…”
Section: Introductionmentioning
confidence: 94%
“…By taking advantage of these structures, several groups have computationally investigated the binding mechanism of fentanyl, and its analogs, at the MOR, but they have not reached a consensus (de Waal et al, 2020;Ellis et al, 2018;Lipinski et al, 2019;Podlewska et al, 2020;Ricarte et al, 2021;Vo et al, 2021). While these studies commonly found that the positively charged nitrogen on the piperidine ring forms a salt bridge with Asp 3.32 (superscripts denote Ballesteros-Weinstein numbering (Ballesteros and Weinstein, 1995)) in the binding site of the MOR, they proposed different binding modes of fentanyl and its analogs.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent example, similar BRET-based studies were elegantly employed for similar analysis by Ehrlich et al,42 investigating ligand bias at the mu opioid receptor where they demonstrate diverse signaling profiles of oliceridine, PZM21 and buprenorphine in neurons. In time, the value of these cellular readouts as predictors of agonist function may be supported by detecting state-dependent structural conformations of MOR induced by biased ligands binding to the receptor[43][44][45] . This does not make their pharmacology less remarkable not does it disprove the hypothesis that ligands may demonstrate active state selectivity.…”
mentioning
confidence: 99%
“…They reported on opioid agonist/NK1 antagonist Tyr-[D-Lys-Phe-Phe-Asp]-Asn-D-Trp-Phe-D-Trp-Leu-Nle-NH 2 and opioid agonist/NK1 agonist Tyr-[D-Lys-Phe-Phe-Asp]-Gln-Phe-Phe-Gly-Leu-Met-NH 2 peptide hybrids with antinociceptive efficacy without inducing analgesic tolerance or constipation in mice after intraperitoneal administration. Research approaches to diminish opioid liabilities take advantage of the current concept of functional selectivity, with biased ligands (agonists and antagonists) as innovative opportunities for opioid pain therapy and use management, subjects reviewed in [12,[15][16][17] and explored in a research article [18].…”
mentioning
confidence: 99%
“…Using molecular docking and molecular dynamics (MD) simulations at three crystal structures of the MOR, Podlewska et al [18] explored the distinct activity profiles at the MOR of morphine (unbiased ligand), PZM21 and SR-17018 (G protein-biased MOR agonists) and fentanyl (β-arrestin2-biased MOR agonist). Several shared and distinct receptor-ligand interaction patterns were identified, and specific amino acids were proposed to be of particular interest when designing new G protein-biased MOR agonists.…”
mentioning
confidence: 99%